Suppressing Polysulfide Shuttling in Lithium–Sulfur Batteries via a Multifunctional Conductive Binder. Issue 10 (9th September 2021) - Chen, Shiming; Song, Zhibo; Ji, Yuchen; Yang, Kai; Fang, Jianjun; Wang, Lu; Wang, Zijian; Zhao, Yan; Zhao, Yunlong; Yang, Luyi; Pan, Feng
Abstract: Exhibiting high specific energy and low cost, lithium–sulfur batteries are considered promising candidates for the next‐generation battery. However, its wide applications are limited by the insulating nature of the sulfur, dissolution of polysulfide species, and large volume change of the sulfur cathode. In this work, a conductive binder, crosslinked polyfluorene (C‐PF) is synthesized and employed in Li–S batteries to enhance the overall electrochemical performance from the following three aspects: 1) possessing high electronic conductivity, C‐PF facilitates lowered areal resistance for the sulfur electrode and leads to an improved rate capability; 2) owing to the cross‐linked polymer structure, favorable mechanical properties of the electrode can be achieved, hence the well‐preserved electrode integrity; 3) forming strong binding with various polysulfide species, C‐PF manages to trap them from diffusing to the Li anode, which greatly improves the cycling stability of Li–S cells. Through designing a multifunctional binder to comprehensively enhance the Li–S cathode, this proposed approach could be broadly applied to fully harness the energy from S redox in addition to cathode material modifications. Abstract : In this work, a multifunctional conductive binder is synthesized and employed in the cathode of Li–S batteries. Exhibiting high electronic conductivity, good adhesive property, and strong binding with the polysulfide species, this conductive binder greatly improves the electrochemical performance of Li–S batteries by efficiently mitigating the polysulfide shuttling effect and electrode disintegration.